Effect of Insulation Thickness on Energy Consumption for Different Shaped Buildings - BOSTANCIOĞLU, ESRA (Springer Nature, 2021)
Control and management of energy consumption are becoming more and more important due to the rapid depletion of fossil energy resources and the increased environmental problems caused by them. A large amount of energy is consumed in the buildings. Therefore, priority is given to applications that reduce the amount of energy consumed during the utilization phase of buildings. Decisions regarding building shape and insulation thickness have a considerable effect on building energy costs. Therefore, this study will analyze the effect of insulation thickness on the energy consumption of residential buildings that have different shapes. The building shape is evaluated with an external envelope area to the building’s gross volume (A/V) ratio and external wall area/floor area (EWA/FA) ratio. 4 building shapes with different external wall area are selected for this study. The maximum and minimum energy costs of each building shapes are calculated based on 14 different envelopes and 8 different orientation alternatives taking into consideration the solar gain. The effects of insulation thicknesses on energy costs for different shaped buildings are determined by comparing energy costs. It will provide pre-design information for future reference for residential buildings with less energy consumption and less environmental pollution. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
▪ Part of the Advances in Science, Technology & Innovation book series (ASTI).
Keywords: Building Envelope; Building Shape; Energy Consumption; Energy Cost; Insulation Thickness